1995
DOI: 10.1111/j.1365-2427.1995.tb00403.x
|View full text |Cite
|
Sign up to set email alerts
|

The critical thermal limits for the bullhead, Cottus gobio, from three populations in north‐west England

Abstract: 1. The objective was to determine the thermal limits for feeding and sur\'ival in the bullhead, Cottus gobio, using juveniles (total length 20-30 mm, live weight 0.5-1.5 g) from one population and adults (50-70 mm, 3.5-5.5 g) from three populations. 2. Fish were acclimated to constant temperatures (3, 7, 10, 15, 20, 25 or 27 °C) and the temperature was then changed at a rate of 1 °C /30 min to determine the critical limits for feeding, survival over 7 days (incipient lethal temperature), or survival for 10 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Thus, changing temperature profiles within rivers arising from climate change can influence the physiology and ecology of a variety of organisms including fish species. The temperatures applied in the present study were far below the upper limit of normal feeding or death for C. gobio which was found to be 27.7°C (Elliott and Elliott 1995). That being so, the current study showed that exposure to temperatures from 4 to 8°C higher than temperature C. gobio would have experienced in the wild during the recrudescence and mating periods significantly influenced its reproduction.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Thus, changing temperature profiles within rivers arising from climate change can influence the physiology and ecology of a variety of organisms including fish species. The temperatures applied in the present study were far below the upper limit of normal feeding or death for C. gobio which was found to be 27.7°C (Elliott and Elliott 1995). That being so, the current study showed that exposure to temperatures from 4 to 8°C higher than temperature C. gobio would have experienced in the wild during the recrudescence and mating periods significantly influenced its reproduction.…”
Section: Discussionmentioning
confidence: 62%
“…Bullhead typically lives in well-oxygenated stream waters from 2 to 16.5°C (Andreasson 1971), whereas Elliott and Elliott (1995) found the critical thermal limits of bullhead to be 4.2 and 27.7°C. It has been selected in our study as a candidate sentinel species reflecting the biodiversity of headwater zones in river networks (Habitats Directive 2007).…”
Section: Introductionmentioning
confidence: 98%
“…CTmax was defined as the point at which ventilation (flaring of the gills) ceased. CTmin was defined as the point at which the righting response was lost; this is a traditional measure of thermal stress tolerance in physiological zoology (Prosser 1973;Bulger and Schultz 1979;Fields et al 1987;ForsterBlouin 1989;Elliot et al 1994;Elliot and Elliot 1995;Meffe et al 1995). Thermal stress was continued until half the individuals in a trial had reached the critical thermal limit (analogous to an LD50).…”
Section: Selection Protocolmentioning
confidence: 99%
“…Temperature plays an important role in the ecology of C. gobio as stated by Elliot and Elliot (1995), and the lack of difference between PA and AA, both in winter and in summer, only means that the two adjacent areas share the same climate.…”
Section: Discussionmentioning
confidence: 99%